Patient-specific implants for maxillofacial defects: challenges and solutions - Nasser Alasseri; Ahmed Alasraj (SpringerOpen, 2020)
Abstract Background Reconstructing maxillofacial defects is quite challenging for most surgeons due to the region's complex anatomy and cosmetic and functional effects on patients. The use of pre-made alloplastic implants and autogenous grafts is often associated with resorption, infection, and displacement. Recent technological advances have led to the use of custom computer-designed patient-specific implants (PSIs) in reconstructive surgery. This study describes our experience with PSI, details the complications we faced, how to overcome them, and finally, evaluates patient satisfaction. Case presentation Six patients underwent reconstruction of various maxillofacial defects arising due to different etiologies using PSI. A combined total of 10 implants was used. PEEK was used to fabricate 8, while titanium was used to fabricate 2. No complications were seen in any patient both immediately post-op and in subsequent follow-ups. All patients reported a high level of satisfaction with the final result both functionally and cosmetically. Conclusion The use of computer-designed PSI enables a more accurate reconstruction of maxillofacial defects, eliminating the usual complications seen in preformed implants and resulting in higher patient satisfaction. Its main drawback is its high cost.